Prevalence and Predictors of Fatigue among Thai Women after COVID-19 Infection - Chanokporn Jitpanya; Surachai Maninet; Pannita Saengkham (Wolters Kluwer Medknow Publications, 2024)
Background: Several people suffered from fatigue after recovering from coronavirus disease 2019 (COVID-19). However, limited studies focused on fatigue in women who recovered from COVID-19 infection. This study aimed to investigate the prevalence of fatigue among Thai women after COVID-19 infection and to identify predictive factors, including depression, anxiety, fear, and insomnia. Materials and Methods: A cross-sectional research design using convenience sampling was conducted from October 2022 to January 2023. A total of 142 Thai women after COVID-19 infection were recruited from two urban communities located in the Bangkok Metropolitan area, Thailand. The participants completed self-reported questionnaires, including the demographic and illness-related data questionnaire, the Depress Anxiety Stress Scales, the Insomnia Severity Index, the Fear of Progression Questionnaire, and the Fatigue Severity Scale. Data were analyzed using mean, standard deviation, range, Pearson's product-moment correlations, and stepwise multiple regression. Results: All (100%) participants returned the questionnaires. After recovering from COVID-19 infection for at least 1 month or longer, 39.40% of the participants reported fatigue. The multiple regression analysis revealed that fear, anxiety, and insomnia collectively contributed to 47% of the variance in the participants' fatigue (R2 = 0.47; p < 0.001). Conclusions: Nearly two-quarters of Thai women after recovering from COVID-19 infection experienced fatigue. To prevent fatigue among Thai women after COVID-19 infection, it is necessary to help them overcome feelings of fear and anxiety. Furthermore, nursing interventions aiming to alleviate insomnia should be implemented.